Pioneer Flintkote Company shingle tower
Since the days of '49, the Pioneer has been to Westerners the symbol of fall that is staunch and progressive. So it is that the "forty-niner" was chosen to symbolize the Pioneer-Flinkote Co., one of the oldest and most progressive firms in the West.